Improved Exploding Properties of Al/Cu Multilayer Initiators. Issue 11 (13th August 2020) - Wang, Yao; Guo, Fei; Wang, Wanjun; Li, Yong; Zhou, Qin; Xing, Zongren; Wang, Liang; Gao, Yuan
Abstract: Reactive multilayer films (RMFs) are widely used for energetic initiator applications, the reaction behavior and mechanism are systematically researched for ignition. Recently, Investigation into exploding plasma fields has been carried out based on Al/Ni RMFs. However, few papers are concerned about Al/Cu multilayers for exploding initiators. In this paper, an investigation on the influence of Al/Cu multilayers additives on initiators is described in detail. The Al/Cu multilayers are deposited by magnetron sputtering technology and their structure is confirmed by scanning electron microscopy. The periodic multilayer structure with controlled thickness is visible. The initiator containing Al/Cu multilayers exhibits improved exploding properties with a short exploding time, low matching charging voltages, and high flyer velocities in comparison with Cu layers or Al layer‐based initiators. Meanwhile, the flyer kinetic energy increase of up to 30 mJ indicates that this improvement could not come from the Al−Cu alloying reaction alone. The 1‐D non‐stationary acceleration model confirms that the composite electrical behavior is a factor contributing to improved flyer kinetic energy. The ultra‐high‐speed camera system is employed to observe the flyer launching process accelerated by the exploding plasma. The smaller barrel diameter is beneficial for controlling the shearing process to keep good integrity of the flyer. Overall, the electrical exploding properties of initiators can be enhanced substantially based on Al/Cu multilayers. Abstract :